Inflammatory Pseudotumour of the Lung: A Case Report and Literature Review - R. Morar; A. Bhayat; G. Hammond; H. Bruinette; C. Feldman (Case Reports in Radiology)
We describe a patient with inflammatory pseudotumour of the lung. He was a young man who presented with haemotysis and the chest X-ray and computerized tomography were indicative of a nonbenign lesion in the right upper lobe. Excision biopsy confirmed the diagnosis of inflammatory myofibroblastic pseudotumour of the lung. This is a rare inflammatory nonneoplastic condition commonly affecting children and young adults.